Associations of cardiometabolic multimorbidity with all-cause dementia, alzheimer’s disease, and vascular dementia: a cohort study in the UK biobank - Zhang, Junrun; Huang, Xiaxuan; Ling, Yitong; Xie, Xiaomei; Zeng, Xiuli; Lyu, Jun; Huang, Li’an (BMC public health, 2025)
Cardiometabolic diseases (CMDs) including type 2 diabetes, heart disease, and stroke, increase the risk of dementia. However, the correlation between CMDs and dementia in different subgroups and the underlying pathophysiological mechanisms linking CMDs with dementia warrant further investigation. This prospective cohort study included a total of 287,748 individuals from the UK Biobank. The outcome measures included all-cause dementia (ACD), Alzheimer's disease (AD) and vascular dementia (VD). Cox regression models and subgroup analyses were used to assess the association between CMD status and dementia, while mediation analysis was evaluated potential roles of inflammatory/metabolic markers in the observed associations. Compared with those without CMD, those with CMD multimorbidity had an elevated risk of ACD (hazard ratio [HR]: 2.27, 95% confidence interval [95% CI]: 1.95-2.63), AD (HR: 1.49, 95% CI: 1.13-1.97), and VD (HR: 3.70, 95% CI: 2.93-4.69). According to the subgroup analyses, the positive correlations between CMDs and ACD, as well as AD, were stronger in individuals who were under the age of 60 or female. Mediation analysis indicated that neutrophils mediated 2.43% of the association of CMDs with ACD, while glucose and hemoglobin A1c mediated 9.22% and 11.85% of the association of CMDs with ACD, respectively. This study further expands the research on cardiometabolic multimorbidity and dementia, highlighting the need for focused attention on specific populations, such as younger individuals and women. Additionally, inflammatory and metabolic biomarkers, as potential mediators, provide critical insights into the complex pathophysiological mechanisms.